AUTOLUMINESCENT ORGANISMS - Samadova Nozima Negmat kizi (Journals Park Publishing, 2022)
The prospect of getting plants that shine in the dark has captured the imagination of scientists and non-professionals. Although the light beam became a useful gene expression marker, the bioluminescence in plants was dependent on the substrate provided from the outside. The evolutionary storage of prokaryotes gene expression mechanism allowed to represent six operon lac genes in chloroplasts and gave plants capable of autonomous irradiation. This study shows that prokaryotes can regenerate and function in complex metabolic pathways plant chloroplasts, and that transplastoma plants can produce light visible to the naked eye.
Keywords: luciferines; luciferases; luciferin firefly